Organic Carbon in Wetland Soil: Seasonal Flooded Forest, Northeastern Thailand - Piyakarn Teartisup; Prapeut Kerdsueb; Suwalee Worakhunpiset (Environment and Natural Resources Journal, 2021)
Seasonal flooded forest is one of the most important wetlands in northeastern Thailand, not only for its abundant biodiversity, but also as a source of carbon sequestration. Organic carbon plays an specially important role in the soil carbon cycle. To reinforce comprehension on soil organic carbon, five profiles in a northeast plateau were observed and determined. The most common trees were Albizzia Odoratissima, Combretum quadrangulare Kurz,and Streblusasper Lour. Thecontents of Soil Organic Carbon (SOC)varied from 3.52 g/kgto 5.90 g/kgin top soil and varied from 4.01 g/kgto 4.60 g/kgin sub soil. There was a close relationship between SOC content and basic soil properties, especially the bulkdensity of both top soil layer and sub soillayer. The distribution of SOC content was harmonized with distribution of plants. In comparative analysis, the flooded forest that composted with a high percentage of vegetation coverage (Khud Tew,Khud Chi Tao)had a significantly higher SOC content. The SOC storage varied from 2.65kg/m2to 4.18 kg/m2. Khud Chi Taocontained the maximum amount of SOC storage, whereas Kwo Chi Yaihad the minimum. Limitation of flooded forest survival concerned over landscape change, particularly plant disappearance and waterlogged shortage. Therefore, vegetation and hydrology management have tobeimplemented practically to retain the existing organic carbon in wetlands and allow the soil to sequester additional carbon.